Radiation Physics for Medical Physicists - Podgorsak, Ervin B. (Biological and Medical Physics, Biomedical Engineering, 2010)
This well-received textbook and reference summarizes the basic knowledge of atomic, nuclear, and radiation physics that professionals working in medical physics and biomedical engineering need for efficient and safe use of ionizing radiation. Concentrating on the underlying principles of radiation physics, it covers the prerequisite knowledge for medical physics courses on the graduate and post-graduate levels in radiotherapy physics, radiation dosimetry, imaging physics, and health physics, thus providing the link between elementary physics on the one hand and the intricacies of the medical physics specialties on the other hand. This expanded and revised second edition offers reorganized and expanded coverage. Several of the original chapters have been split into two with new sections added for completeness and better flow. New chapters on Coulomb scattering; on energy transfer and energy absorption in photon interactions; and on waveguide theory have been added in recognition of their importance. Others training for professions that deal with ionizing radiation in diagnosis and treatment as well as medical residents, students of technology and dosimetry,and biomedical engineering will find many sections interesting and useful for their studies. It also serves as excellent preparatory materials for candidates taking professional certification examinations in medical physics, medical dosimetry, and in medical specialties such as radiotherapy, diagnostic radiology, and nuclear medicine. From reviews of the first edition: "Any instructor teaching an introductory graduate-level course on the principles of medical physics should consider this book for adoption as a text... cover[s] the principles themselves, and it covers them very well." (Medical Physics, January 2006) "... a delight and ready-reference also to seasoned practitioners... This textbook, based on notes the author 'developed over the past 25 years of teaching radiation physics to MSc and PhD students in medical physics at McGill University' is a real gem for the bookshelf of anyone already professional working in the radiation sciences..." (John H. Hubbell, Radiation Physics and Chemistry) "...for the theory of radiation physics at a fundamental level, Podgorsak's book provides a wonderful resource presented in a well organized and easy to learn manner, in a way not found in any other text... " (Jake van Dyk, London Regional Cancer Program, Can. Med Phys Newsletter (July 2006).